Novel gas aggregation cluster source based on post magnetron. Issue 9 (26th July 2021) - Nikitin, Daniil; Hanuš, Jan; Pleskunov, Pavel; Krtouš, Zdeněk; Ali‐Ogly, Suren; Tafiichuk, Renata; Biliak, Kateryna; Protsak, Mariia; Valter, Jan; Vyskočil, Jiři; Choukourov, Andrei; Biederman, Hynek
Abstract: In this communication, a new gas aggregation cluster source is introduced equipped with post cylindrical magnetron. The rotation of magnetic circuit improves the usage of cylindrical copper target in terms of its homogenous consumption. Copper nanoparticles were successfully synthesized. Their deposition rate fluctuates at slow rotations of magnetic circuit. Cyclic trapping and release of nanoparticles from electrostatic capture zones are likely responsible for this effect. The instabilities are not observed at higher rotation speeds. The argon flow is found to be very complex within the cluster source; however, it seems crucial for its operation. The efficiency of transport of nanoparticles and their size increase with gas flow. The highest values of deposition rate of around 19 mg/h are obtained. Abstract : The post cylindrical magnetron is applied as a source of atomic vapors in the gas aggregation cluster source. The efficiency of target utilization is improved by the rotation of the magnetic circuit. The influence of rotation speed, discharge current, and argon flow rate on the deposition of copper nanoparticles is studied in detail, and the last parameter is found to be crucial. The effect of nanoparticle trapping in plasma torus is revealed. The maximal deposition rate is 19 mg/h.